BIOLOGICAL INVESTIGATION OF THE SAFETY PROFILE OF TWO SILICONE ALIGNERS - A PIVOTAL STEP IN THE PROGRESS OF ORTHODONTIC TREATMENTS - Romina-Georgiana Biță; Silviu Brad; Iasmina-Alexandra Predescu; Raluca-Adriana Milutinovici; Camelia Szuhanek; Ramona Popovici; Stefania Dinu (Romanian Journal of Oral Rehabilitation)
Aim of the study According to the World Health Organization, malocclusion is one of children's most common dental problems. Many children visit dentists early, requiring long-term treatment due to misaligned teeth. Silicone aligners represent modern alternative treatments to traditional orthodontic appliances due to the soft and flexible material from which they are made and the effectiveness they have proven over the years. The present study aims to investigate the biosafety profile of four silicone aligners (A1, A2, A3, and A4) from three different manufacturers by in vitro and in ovo assays. Materials and methods In this study, four silicone aligners were immersed in artificial saliva at a neutral pH for seven days. Subsequently, four different dilutions (1:8, 1:4, 1:2, and 1:1) were then prepared and tested in vitro on HaCaT and JB6 Cl 105 41-5a cell lines to analyze their effects on cell viability and potential irritant effect on the blood vessels of the chorioallantoic membrane. Results The results showed that after 48 hours of exposure to A1, A2, A3, and A4, the viability of HaCaT and JB6 Cl 105 41-5a cell lines remained over 70%, which demonstrates, according to ISO Standard 10993-5:2009, that these aligners are not considered cytotoxic. Additionally, regarding cell morphology, the four dental devices did not induce significant changes in the appearance of the nuclei. Furthermore, the potential irritant effect of A1, A2, A3, and A4 on the chorioallantoic membrane was evaluated. It was observed that they did not produce changes in the blood vessels, with an irritation score of 0.070, categorizing them as non-irritant agents. Conclusions This study confirms the biosafety profile of the four dental aligners: A1, A2, A3, and A4.